Nutritional composition and sensory attributes of Alaskan flatfishes compared to plaice (Pleuronectes platessa). (27th December 2012) - Karl, Horst; Manthey‐Karl, Monika; Ostermeyer, Ute; Lehmann, Ines; Wagner, Hubertus
Summary Proximate composition, fatty acids profiles and other nutritional values were evaluated for fillets of Limanda aspera (yellowfin sole), Lepidopsetta bilineata (southern rock sole) and Lepidopsetta polyxystra (northern rock sole) and compared to North Sea plaice (Pleuronectes platessa). Additional information is given on the composition of fillets from arrowtooth flounder (Atheresthes stomias). Plaice (0.8% lipid) and Alaska soles (1.0–1.2% lipid) can be classified as lean species, resulting in low 0.3–0.5 g ∑EPA+DHA/100 g muscle, although the fatty acid profiles of the extracted lipids were characterised by high amount of n‐3 fatty acids (33.2–47.3%). Arrowtooth flounder belong to the medium‐fat species (4.3%). Taurine was the most prevalent free amino acid; mean values ranging between 221 mg100 g−1 and 247 mg100 g−1 wet weight. The selenium content varied between 130 and 310 μg kg−1 ww. Sensory attributes of Southern and Northern rock sole were comparable to plaice.